New iterative method for solving nonlinear evolution equations - Selamat, Mat Salim (Universiti Teknologi MARA, 2009)
This paper discusses the implementation o fa new iterative method for solving some nonlinear evolution equations. The results obtained are compared with those obtained by other iterative methods such as homotopy perturbation and variational iteration methods.